Variation between Antagonistic Activity of Rosmarinus officinalis Essential Oil and Biosynthesized Silver Nanoparticles from the Essential Oil against Some Fungi - Al Bahrani, Rusol M; Najem, Ali M; Abed, Ibrahim J (Al-Nahrain Journal of Science, 2018)
This study was conducted to evaluate the antagonistic activity of  Rosmarinus officinalis L. (Rosemary) essential oil at different concentrations (500, 1000, 2000 or 3000 ppm) against three different fungi (Aspergillus niger, Penecillium notatum and Candida sp.), these isolates were isolated from air. On the other hand, a combination between the Rosemary essential oil and synthesized nanoparticles were tested against the isolated fungi. Results revealed that Rosemary essential oil exhibited the highest antifungal potentiality comparing to the antagonisty of the biosynthesized nanoparticles. The concentration 3000 ppm of the essential oil showed 100% mycelial growth inhibition of all the fungi. Aspergillus niger was the most sensitive which showed no growth in the concentrations 1000, 2000 or 3000 ppm. The biosynthesized silver nanoparticles from Rosemary essential oil exhibited a considerable fungicidal activity against all the fungal isolates. The inhibition of all fungal isolates increased as the concentrations of the synthesized silver nanoparticles increased. Asp. niger was the most sensitive fungi to the inhibitory impact of the Rosemary nanoparticles and Penicillium notatum manifested mild response, while Candida sp. was less sensitive.